Investigation of the Relationship Between Goal Orientation and Life Satisfaction of Tennis Players Participating in Local Tournaments - Abdil Arı (Selcuk University, 2022)
This study was conducted to investigate the relationships and differences between the goal orientations and life satisfaction of tennis players. A total of 80 athletes, 66 men and 14 women, participated in the Silifke Municipality Sports Club 2021 spring tennis tournament voluntarily. The personal information form developed by the researchers to reach the data of the study, the 13-question "Duty and Ego Orientation Scale in Sports (SGEYÖ)" developed by Duda in 1992 and the Turkish adaptation of Toros in 2001, and the Orphan Scale developed by Larsen and Griffin in 1985. The 5-question "Satisfaction with Life Scale", which was adapted into Turkish in 1991, was used. According to the results of the research; The inter-variable relations of all participants are presented as correlation coefficients. Here, when the significance relationships in terms of double-ended evaluation are examined, there is a significant relationship between ego orientation scores and task orientation scores (r=0,238; p lt;0,05). In addition, age variable and task orientation scores (r=-0,407; p lt;0,01) and life satisfaction scores (r= 0,266; p lt;0,05) there is a significant relationship between. There is no significant relationship between other variables. (p gt;0,05).